Investigate the antagonistic effect of flumazenil on the recovery of patients above the age 50 years from anaesthesia receiving Benzodiazepine products (1993) - Mehry Monemy (Iran University of Medical Sciences, 1999)
A quasi. experimental study was conducted to investigate the antagonistic effect of Flumazenil on the   recovery of patients above the age 50 year from anaesthesia receiving Benzodiazepine products in one of   Iran Medical Sciences University hospital's operating rooms .   A total of sixty middle aged patients were selected sequentially . Thirty of them (12 females and 18 males )   were in the control group and the other thirty (15 female s and 15 males) in the study group . All were   out-patients scheduled for a short cataract surgery.   The instrument was a check-list . The information was collected from the patients, records •   haemodynamic laboratory reports and an interview with the subject . The findings were presented in 16   Tables, further descriptive and inferal statistical rests (t2) were employed for analytical procedures.   The results indicated that IV. Injection of Flumazenil immediately after the surgical procedure helps   stabilize patients' vital signs (pulse , respiration and blood pressure ) approaching preoperative measures and   those of the Benzodiazepine injection patients ' recovery , Regaining consciousness was promoted as well .   Based on the findings the researcher recommends certain nursing measures for implication in anaesthesia and makes suggestions for further research